Innovating climate adaptation tracking: Climate action’s groundbreaking research on tracking adaptation is shaping adaptation policy agendas from Africa to the globe. - Nowak, Andreea C.; Njuguna, Lucy; Rosenstock, Todd (2024)
The Climate Action team's research on climate-adaptation tracking (shortened to ‘adaptation tracking’ hereafter) has positioned its researchers as influential global experts. Actively engaged in international fora, their expertise is in high demand. They provide technical support to African negotiators regarding climate action; contribute to the United Nations Environment Program (UNEP) Adaptation Gap Report; and co-chair the agriculture committee of the International Platform for Adaptation Metrics (IPAM). These help shape adaptation tracking agendas at national, continental and global levels. Additionally, their policy engagements and on-demand scientific outputs have elevated CGIAR’s profile in climate-change adaptation.